A Deep Learning Model Based on Islamic Spirituality : Improving Students’ Academic Competence and Religious Character - Nakhma’ussolikhah Nakhma’ussolikhah; Septi Gumiandari; Eti Nurhayati; Nurlaela Nurlaela (Eduprof : Islamic Education Journal, 2026)
Religious Education learning in health schools aims to prepare health workers with academic competence and religious character. Based on preliminary research, it was found that learning Islamic religious education has not yet optimal the results, and not yet There is A model that can be used as a reference to improve learning outcomes. An in-depth learning model Islamic spiritual education-based learning can be a solution to provide guidance to teachers in improving students' academic competence and religious character. This research aims to develop an in-depth learning model. based on Islamic spirituality. The development of this model is reinforced by the need for innovation and research-based development within the framework of Analysis, Design, Development, Implementation, Evaluation, Population, and Development. This study involved 219 students and a sample of 35 11th-grade students at the Pharmacy Vocational High School. The qualitative data collection techniques used were observation of the Islamic Religious Education (PAI) learning process and interviews with Islamic Religious Education (PAI) teachers, principals, students, and teachers. And questionnaire to student For quantitative data. Qualitative data analysis This study uses NVivo version 15, and quantitative analysis uses correlation formulas, linear regression, and MANOVA with the help of the SPSS 23 application. Conclusions from the research results: (1) Design from PAI deep learning developed into 3 element base That is IQ, EQ, SQ (2) Implementation of deep learning models includes planning and implementation. In planning, students are conditioned and provided with media and teaching materials. In implementation, role-playing techniques are used. and PJBL (3) Evaluation of the effectiveness of the results of the Deep Learning model Based on NVivo analysis, it shows that students' academic competency indicators are dominated by cognitive and affective aspects. Data processing using the Group Query feature in NVivo shows a strong relationship between academic competency indicators and religious character.